Phase II study of liposomal doxorubicin, docetaxel and trastuzumab in combination with metformin as neoadjuvant therapy for HER2-positive breast cancer. (February 2021) - Rocca, Andrea; Cortesi, Pietro; Cortesi, Laura; Gianni, Lorenzo; Matteucci, Federica; Fantini, Lorenzo; Maestri, Antonio; Giunchi, Donata Casadei; Cavanna, Luigi; Ciani, Rosa; Falcini, Fabio; Bagni, Antonella; et al.
Background: The aim of this study was to improve activity over single human epidermal growth factor receptor 2 (HER2)-blockade sequential neaodjuvant regimens for HER2-positive breast cancer, by exploiting the concomitant administration of trastuzumab, taxane and anthracycline, while restraining cardiac toxicity with use of liposomal doxorubicin, and by adding metformin, based on preliminary evidence of antitumor activity. Patients and methods: This multi-center, single-arm, two-stage phase II trial, assessed the safety and the activity of a new treatment regimen for HER2-positive, early or locally advanced breast cancer. Patients received six 21-day cycles of non-pegylated liposomal doxorubicin, 50 mg/m 2 intravenously (i.v.) on day 1, docetaxel, 30 mg/m 2 i.v. on days 2 and 9, trastuzumab, 2 mg/kg/week i.v. on days 2, 9, and 16 (with 4 mg/kg loading dose), in association with metformin 1000 mg orally twice daily. The primary endpoint was the rate of pathological complete response (pCR) in the breast and axilla (ypT0/is ypN0). A subgroup of patients performed a 3-deoxy-3-18F-fluorothymidine positron emission tomography (FLT-PET) at baseline and after one cycle. Results: Among 47 evaluable patients, there were 18 pCR [38.3%, 95% confidence interval (CI) 24.5–53.6%]. A negative estrogen-receptor status, high Ki67, and histological grade 3 were related with pCR, although only grade reached statistical significance. FLT-PET maximum standardized uptake value after one cycle was inversely related to pCR in the breast (odds ratio 0.29, 95% CI 0.06–1.30, p = 0.11). Toxicity included grade 3–4 neutropenia in 70% and febrile neutropenia in 4% of patients, grade 1–2 nausea/vomiting in 60%/38%, and grade 3 in 4%/2%, respectively, grade 1–2 diarrhea in 72%, and grade 3 in 6%. There were two cases of reversible grade 2 left-ventricular ejection-fraction decrease, and one case of sharp troponin-T increase. Conclusions: The concomitant administration of trastuzumab, liposomal doxorubicin, docetaxel, and metformin is safe and shows good activity, but does not appear to improve activity over conventional sequential regimens.